Cyclic behaviour of external diaphragm joint to CHS column with built‐in replaceable links. Issue 4 (November 2016) - Khador, Majd; Chan, Tak‐Ming
Abstract: A series of full‐scale laboratory experiments was conducted to investigate the cyclic behaviour of an external diaphragm joint between a steel I‐beam and a circular hollow section column. The joint incorporated two diaphragm plates (DPs) welded to the column's external wall and bolted to the flanges of the beam using tapered cover plates (TCPs). The joint was designed to limit yielding and plastic hinging of the TCPs while the other joint components remained elastic. This is necessary if the joint is to qualify for use in structures classified in the damage control structural performance range according to FEMA 356. Two parameters of the TCPs are investigated in this paper: steel grade and bolt preload force. The use of higher steel grades was found to impose undesirable higher strain demands on the beam and DPs and dissipate less energy than the joints with the lower grade. A controlled reduction in the bolt preload force allowed connection slippage to occur beyond the serviceability limit, created an additional energy dissipation fuse and allowed rotation of the plastic hinge region to exceed the 25 mrad required for medium ductility class structures.